'Me and Not-Me': Folk Songs, Narrative Perspectives, and The Gender Imaginary in Angela Carter's Shadow Dance. (3rd August 2020) - Paulusma, Polly
Abstract: It is a little-known fact that Angela Carter was a traditional folk singer during the 1960s, that she played the English concertina, and that she co-founded a folk club in Bristol with her first husband, Paul Carter. A newly unearthed private archive of her folk song notes from the decade, which includes her musical notations and a recording of her singing, allows us to develop new understandings of her folk praxis and, when laid alongside her private journal entries, the folk album sleeve notes she penned, her undergraduate dissertation, and other unpublished papers, a whole host of possible new readings of her literary work emerges. This essay explores just one: gender fluidity in folk song performance and its impact upon Carter's interpretations of gender identity in her debut novel, Shadow Dance. I will suggest that Carter learned gender ambiguity from her folk singing, and that her experience of singing afforded her freedoms to explore versions of sexual performance and gendered selfhood through male characters. More broadly, I will suggest that she buried musical folk song features into the structures of her writing to present her prose as a form of audial performance.